Premessa: Seminario di Studi Dante e il fumetto (Itinera, 2023)
The University of Turin has organized a series of events to celebrate the seventh centenary of Dante's death. The final event included a seminar on Dante and comics, a figurative comment which, despite the different purposes and different audiences, still reminds us that Dante's iconic poetry favors illustrations, in which excellent illuminators have distinguished themselves from the very beginning.
Keywords: Dante, comics, poetry, illustrations